2020
DOI: 10.1080/15548627.2020.1839286
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy receptor OPTN (optineurin) regulates mesenchymal stem cell fate and bone-fat balance during aging by clearing FABP3

Abstract: Senile osteoporosis (OP) is often concomitant with decreased autophagic activity. OPTN (optineurin), a macroautophagy/autophagy (hereinafter referred to as autophagy) receptor, is found to play a pivotal role in selective autophagy, coupling autophagy with bone metabolism. However, its role in osteogenesis is still mysterious. Herein, we identified Optn as a critical molecule of cell fate decision for bone marrow mesenchymal stem cells (MSCs), whose expression decreased in aged mice. Aged mice revealed osteopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 49 publications
0
64
0
Order By: Relevance
“…For example, the deficiency of TSC1 , a positive inducer of autophagy, resulted in bone loss through suppressing osteogenic differentiation, elevating the osteoclast differentiation and adipogenic differentiation 42 . The autophagy receptor OPTN controlled the cell fate switch between adipocytes and osteoblasts in BMSCs 26 . Here, we validated Scara3 facilitating autophagy.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…For example, the deficiency of TSC1 , a positive inducer of autophagy, resulted in bone loss through suppressing osteogenic differentiation, elevating the osteoclast differentiation and adipogenic differentiation 42 . The autophagy receptor OPTN controlled the cell fate switch between adipocytes and osteoblasts in BMSCs 26 . Here, we validated Scara3 facilitating autophagy.…”
Section: Discussionmentioning
confidence: 71%
“… 42 The autophagy receptor OPTN controlled the cell fate switch between adipocytes and osteoblasts in BMSCs. 26 Here, we validated Scara3 facilitating autophagy. Further study revealed that the deficiency of Scara3 exacerbated the osteogenesis‐adipogenesis imbalance in BMSCs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a rat model of osteoporosis, reduced levels of autophagy in osteoblasts have been reported (Tang et al, 2019). optn À/À mice show reduced ability to eliminate FABP3 (fatty acid binding protein 3, muscle and heart) by selective autophagy linked to impaired osteogenesis and increased bone loss, thus supporting the notion that decreased expression of OPTN during aging might lead to osteoporosis (Liu et al, 2020c). In contrast, genetic…”
Section: Bone Disordersmentioning
confidence: 91%
“…RANKL, an osteoclastogenic cytokine, has been shown to be increasingly secreted by MSCs in aged mice ( Lin et al, 2017 ), leading to bone loss ( Kim et al, 2020 ). Cellular senescence also leads to a decrease in Optineurin (OPTN), an autophagy receptor therefore contributing to osteoporosis alongside with accumulation of the OPTN substrate fatty acid binding protein 3 (FABP3) ( Liu et al, 2020 ).…”
Section: Msc Changes In Aging Bone Marrowmentioning
confidence: 99%